The Politics of Apologies and Colonial Aphasia: Dutch Colonial Violence in Indonesia’s War of Independence (1945–1949) - Utama, Muhammad Anugrah (Politikon: The IAPSS Journal of Political Science, 2025)
The colonial violence in Indonesia’s War of Independence (1945–1949) remains a controversial subject in Dutch society up to this day. In 2022, former Dutch prime minister Mark Rutte apologised for the “systematic and widespread extreme violence,” prompting renewed debate on how official statements and apologies function as forms of hegemonic remembrance. This paper revisits Ann Stoler’s concept of colonial aphasia and Gloria Wekker’s concept of white innocence. It examines several critical moments that reveal the persistent difficulties of remembering and forgetting colonial violence. Each section presents primary sources related to a specific critical event, followed by speeches, statements, or reports issued by the Dutch government. This research highlights how reports, statements, and apologies have historically been instrumentalised by the Dutch state to construct a nationally accepted hegemonic narrative—one that acknowledges colonial violence while simultaneously evading deeper accountability.